Genomic islands 1 and 2 play key roles in the evolution of extensively drug-resistant ST235 isolates of Pseudomonas aeruginosa - Piklu Roy Chowdhury (Open Biology, 2016)
Pseudomonas aeruginosa are noscomially acquired, opportunistic pathogens that pose a major threat to the health of burns patients and the immunocompromised. We sequenced the genomes of P. aeruginosa isolates RNS_PA1, RNS_PA46 and RNS_PAE05, which displayed resistance to almost all frontline antibiotics, including gentamicin, piperacillin, timentin, meropenem, ceftazidime and colistin. We provide evidence that the isolates are representatives of P. aeruginosa sequence type (ST) 235 and carry Tn6162 and Tn6163 in genomic islands 1 (GI1) and 2 (GI2), respectively. GI1 disrupts the endA gene at precisely the same chromosomal location as in P. aeruginosa strain VR-143/97, of unknown ST, creating an identical CA direct repeat. The class 1 integron associated with Tn6163 in GI2 carries a blaGES-5–aacA4–gcuE15–aphA15 cassette array conferring resistance to carbapenems and aminoglycosides. GI2 is flanked by a 12 nt direct repeat motif, abuts a tRNA-gly gene, and encodes proteins with putative roles in integration, conjugative transfer as well as integrative conjugative element-specific proteins. This suggests that GI2 may have evolved from a novel integrative conjugative element. Our data provide further support to the hypothesis that genomic islands play an important role in de novo evolution of multiple antibiotic resistance phenotypes in P. aeruginosa.